1995
DOI: 10.1111/j.1442-9993.1995.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cactus size and previous infection on bird deposition of mistletoe seeds

Abstract: Tristerix aphyllus (Loranthaceae) is a bird‐dispersed mistletoe that infects several cactus species in central and north‐central Chile. At Las Chinchillas National Reserve it parasitizes two species of columnar cacti (Echinopsis chilensis and Eulychnia acida) and its seeds are dispersed exclusively by the Chilean mockingbird Mimus thenca. The prevalence of T. aphyllus on cacti depended on host species and size. Echinopsis chilensis was parasitized at a higher, and E. acida at a lower, frequency than expected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several studies have shown mistletoe density to be positively correlated to host tree size (Overton, 1994, Martinez del Rio et al, 1995, Lei 1999Aukema & Martinez del Rio, 2002;Shaw et al, 2005;Matula et al, 2015;Pérez-Crespo et al, 2016). Consistent with those studies, we found mistletoe is likely to occur in greater densities on larger host trees.…”
Section: Densitymentioning
confidence: 99%
“…Several studies have shown mistletoe density to be positively correlated to host tree size (Overton, 1994, Martinez del Rio et al, 1995, Lei 1999Aukema & Martinez del Rio, 2002;Shaw et al, 2005;Matula et al, 2015;Pérez-Crespo et al, 2016). Consistent with those studies, we found mistletoe is likely to occur in greater densities on larger host trees.…”
Section: Densitymentioning
confidence: 99%